2008
DOI: 10.1016/j.pain.2008.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Acidic buffer induced muscle pain evokes referred pain and mechanical hyperalgesia in humans

Abstract: While tissue acidosis causes local deep-tissue pain, its effect on referred pain and mechanical muscle hyperalgesia is unknown. The aim of this study was to investigate a human experimental acidic muscle pain model using a randomized, controlled, single-blinded study design. 72 subjects (36 female) participated in three visits, each involving one 15 min intramuscular infusion into the anterior tibialis muscle: acidic phosphate buffer (5.2 pH) at 40 ml/hr (N=69) or 20 ml/hr (N=54), normal phosphate buffer (7.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 68 publications
3
71
2
2
Order By: Relevance
“…The lack of change in PPTs at remote sites may signify that more persistent changes in the nociceptive pathways (ie, nonspecific widespread pain) had not taken place. 40 This is consistent with the findings of Frey-Law et al, 14 who, following induced muscle pain, demonstrated decreased PPTs at the site of induced pain and within the area of pain expansion (ie, regional central sensitization) but not at remote sites.…”
Section: Quantitative Sensory Testingsupporting
confidence: 85%
“…The lack of change in PPTs at remote sites may signify that more persistent changes in the nociceptive pathways (ie, nonspecific widespread pain) had not taken place. 40 This is consistent with the findings of Frey-Law et al, 14 who, following induced muscle pain, demonstrated decreased PPTs at the site of induced pain and within the area of pain expansion (ie, regional central sensitization) but not at remote sites.…”
Section: Quantitative Sensory Testingsupporting
confidence: 85%
“…Examples given are NGF, hypertonic saline, capsaicin, glutamate, bradykinin, serotonin, histamine, prostaglandin, ATP, and phosphate buffer. In this review, only the most widely used methods are described, and the reader is referred to other papers for more specific information (Babenko et al, 1999a,b;GravenNielsen and Arendt-Nielsen, 2003;Mørk et al, 2003;Frey Law et al, 2008). Each substance is described individually and general advantages and limitations are given at the end of this section.…”
Section: B Muscle and Bonementioning
confidence: 99%
“…63 Recently, this observation has been confirmed in humans where intramulcular injection of an acidic buffer induced mechanical muscle hyperalgesia. 64 Tissue acidosis is an important feature in many clinical conditions. 65 This observation has prompted the pharmaceutical industry to start the development of activation of acid-sensing ion channel receptor antagonists, and the acid model can act as a biomarker in this area.…”
Section: Acid (Low Ph)mentioning
confidence: 99%